Utilization of Articulate Storyline as Interactive Learning Media to Improve the Study Motivation of College Students - Gamilla Nuri Utami; Heru Agung Saputra; Berti Yolida (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
A teacher is required to be able to develop a learning approach that is in line with the today’s student learning styles. This study was aimed at finding out the utilization of articulate storyline to increase the student motivation in the interactive learning of the history of chemistry. The research subjects were 66 college students divided into groups A and B with 33 students for each. The research method was the research interviews (a qualitative research), where the problem formulation was if (or not) use of the articulate storyline as interactive learning media can improve the student learning motivation. The instruments for the data collection were the observation sheets. 75.8, 15.2, and 9.1% of the students in group A stated that the articulate storyline improved the study motivation in very high, high, and the medium levels, respectively. Meanwhile, 33.3%, 54.5%, and 9.1% of group B students declared that their learning motivation improved in very high, high, and the medium levels, respectively. In addition, 3% of the students in this group revealed that the articulate storyline affected their learning motivation in the low level. Conclusively, the interactive learning media of the articulate storyline could improve the learning motivation of Chemical Education students on the history of chemistry.Keywords: articulate storyline, college students, learning media, learning motivation,online learning system